The IOS Annual Volume 21. "Carrying a Torch to Distant Mountains" - Cohen, Yoram; Gilan, Amir; Sheyhatovitch, Beata; Cerqueglini, Letizia (The IOS Annual., 2022)
The IOS Annual Volume 21: "Carrying a Torch to Distant Mountains" , brings forth cutting-edge studies devoted to a wide array of fields and disciplines of the Middle East. The three sections-the Ancient Near East, Semitic Languages and Linguistics, and Arabic Language and Literature-include sixteen articles. In the Ancient Near East section are studies devoted to Babylonian literature (Gabbay and Wasserman; Ayali-Darshan), history (Cohen and Torrecilla), and language (Zadok). The Semitic Languages and Linguistics section contains discussions about comparative Semitics-Egyptian and Modern South Arabic (Borg; Cerqueglini), Aramaic dialects (Khan; Stadel), Palestinian Arabic (Arnold; Procházka), and Tigre and Ethiosemitic languages (Voigt). The final section of Arabic Language and Literature is devoted to ʿArabiyya and its grammarians (Dror, Versteegh, Sheyhatovitch, Kasher, and Sadan)